2004
DOI: 10.1002/chem.200400400
|View full text |Cite
|
Sign up to set email alerts
|

cis/trans Photoisomerization of Secondary Thiopeptide Bonds

Abstract: The reversible cis/trans photoisomerization of secondary thiopeptide bonds has been systematically studied with UV-visible absorption, capillary electrophoresis, 1H NMR spectroscopy, and circular dichroism methods. It was found that the concentration of the cis conformers could be increased from less than 1 % in the thermal equilibrated solution to up to 20 % in the photostationary state. The rotational barriers of the thiopeptide bond and the pH dependence of the isomerization rates were also studied. The qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…[25,26] Also, geometric constraints imparted on the azobenzene moiety when incorporated into macrocycles can markedly affect thermal relaxation rates, as well documented with cyclic azobenzene peptides ( Table 2). [23] It should be noted that the [27] and hemithioindigos, [28] which have been developed in the group of Karola Rück-Braun, as well as secondary thioamide bonds, [29][30][31] which would be "minimal invasive" chromophores.…”
Section: Azobenzene-based Photoswitchesmentioning
confidence: 98%
“…[25,26] Also, geometric constraints imparted on the azobenzene moiety when incorporated into macrocycles can markedly affect thermal relaxation rates, as well documented with cyclic azobenzene peptides ( Table 2). [23] It should be noted that the [27] and hemithioindigos, [28] which have been developed in the group of Karola Rück-Braun, as well as secondary thioamide bonds, [29][30][31] which would be "minimal invasive" chromophores.…”
Section: Azobenzene-based Photoswitchesmentioning
confidence: 98%
“…This results in a red shift of the p-p* absorption band of the substituted peptide unit, allowing for selective excitation and isomerisation of the thiopeptide bond. [12][13][14] The thiopeptide unit maintains the planar geometry of the oxopeptide, and the main types Abstract: The conformations of a protected tetrathiopeptide have been analysed by isotope labelling and two-dimensional infrared spectroscopy (2D-IR). It has been found that Boc-AlaGly(=S)-Ala-Aib-OMe in acetonitrile, as well as its oxopeptide analogue, can adopt a hydrogen-bonded loop conformation in coexistence with less restricted structures.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] On irradiation at 248 nm we can thus enhance the concentration of peptides in the cis state until a photoequilibrium is established by reverse photoisomerisation and thermal relaxation. The difference between the FTIR spectra recorded before and during UV irradiation (thick solid lines in Figure 7) show the absorption bands in the trans state as negative signals and the absorption bands in the cis state as positive signals.…”
mentioning
confidence: 99%
“…The other possibility for photochemical process is the well-known cis-trans isomerization of azobonds that leads to decrease of color intensity [39][40][41][42][43]. As we reported earlier [44], cis-trans isomerization of bis-azo precursor (3a) was leaded to reduction of color intensity.…”
Section: Accepted Manuscriptmentioning
confidence: 85%